Regional development strategy of tourism in Slovakia - Vongrej, Marián (Hotel and Tourism Management, 2014)
This paper is dedicated to the development of tourism in the Slovak Republic. Slovakia is a relatively small country, but with a great natural and cultural potential. Unfortunately, the Slovaks do not apply this potential enough in greater satisfaction and attendance of foreign tourists, as well as the locals. We believe that services are generally not adequate to the tourist price range. The implementation of structural fonds in Slovakia is also insufficient. Therefore, we think that the private and public sector should give more importance to theoretical and practical aspects of knowledge management.